Behavioural consistency in the dyeing poison frog, Dendrobates tinctorius - Alanen, Emmi (2020)
The behaviour of an individual organism is a combination of previous experiences and genetic factors. In some situations, a behaviour of an individual may be repeatable or consistent. For my Master’s thesis, I studied the consistency of behaviour in amphibians in two life stages. Specifically, I used the dyeing poison frog (Dendrobates tinctorius), a species who is cannibalistic during its larval stage, and transitions from an aquatic to terrestrial habitat across metamorphosis. The aim of my project was to find out if behaviour is consistent within larval and juvenile stages of D. tinctorius frogs. Based on previous studies showing consistency in amphibian behaviour, I investigated whether (1) D. tinctorius tadpoles have consistency in their aggressive behaviour; and (2) D. tinctorius individuals show consistency in activity after metamorphosis. During the frog’s larval stage, I conducted two aggression trials where individual behaviour was observed in the presence of a conspecific. Likewise, froglet behaviour was observed individually in two consecutive trials where the movements of an individual were observed in a novel environment. No repeatability was found in larval behaviour. In juveniles, activity was found to be repeatable at the family level. None of the studied behaviours was consistent at individual level. This study shows that there is some behavioural consistency in D. tinctorius, but further research is needed in order to show repeatability at individual level, or across life stages.